Ultrafast formation and dynamics of interlayer exciton in a large-area CVD-grown WS2/WSe2 heterostructure. (15th November 2018) - Yu, Yang; Wang, Ziyu; Wei, Jingle; Zhao, Wanying; Lin, Xian; Jin, Zuanming; Liu, Weimin; Ma, Guohong
Abstract: A WS2 /WSe2 heterostructure is constructed by stacking a WS2 monolayer on the top of WSe2 monolayer fabricated with chemical vapor deposition (CVD) method. Ultrafast transient spectroscopy is used to demonstrate the ultrafast charge transfer and interlayer exciton dynamics in the heterostructure. When the WS2 /WSe2 heterostructure was photoexcitated at 617 nm (2.01 eV) to excite the A-exciton transition of WS2, an ultrafast photobleaching was observed around the WSe2 A-exciton transition at 749 nm. The bleaching signal lasts several nanoseconds, which is much longer than the A-exciton lifetime in both the WS2 and WSe2 monolayer film. Moreover, by selectively photoexciting the A-exciton of WSe2 at 749 nm in the heterostructure, an ultrafast photobleaching occurs around the WS2 A-exciton transition, the recovery of the bleaching shows a single exponential relaxation with typical time constant of ~1.8 ps. The very fast relaxation in the heterostructure probing around 620 nm is indicative that rich defect states exist below the conduction band in WS2, which can efficiently trap these electrons transferred from the WSe2 upon photoexcitation. Our spectroscopic results reveal that our CVD-grown WS2 /WSe2 bilayer film has a type II heterostructure in nature at room temperature. With photoexcitation, electrons and holes can be separately confined in the WS2 and WSe2 layer, respectively; as a result, interlayer excitons are formed.